2013
DOI: 10.1371/journal.pone.0078722
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Breast Cancer: Mammographic Features and Mortality Risk in a Population of Healthy Women

Abstract: BackgroundBreast fibroglandular (dense) tissue is a risk factor for breast cancer. Beyond breast cancer, little is known regarding the prognostic significance of mammographic features.MethodsWe evaluated relationships between nondense (fatty) breast area and dense area with all-cause mortality in 4,245 initially healthy women from the Breast Cancer Detection Demonstration Project; 1,361 died during a mean follow-up of 28.2 years. Dense area and total breast area were assessed using planimeter measurements from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Our results support the idea of a differential effect of breast density, with high breast density being a risk factor for breast cancer but not necessarily conferring a worse prognosis in diagnosed cancers. Some authors have reported that non-dense breasts, which are associated with a higher percentage of fatty tissue, may be linked to lipogenic regulation pathways of prognostic significance (32). This idea is supported by the results of Gierach and colleagues, (30) who found an increased risk of death among obese women with non-dense breasts in a large cohort of U.S. women.…”
Section: Discussionmentioning
confidence: 86%
“…Our results support the idea of a differential effect of breast density, with high breast density being a risk factor for breast cancer but not necessarily conferring a worse prognosis in diagnosed cancers. Some authors have reported that non-dense breasts, which are associated with a higher percentage of fatty tissue, may be linked to lipogenic regulation pathways of prognostic significance (32). This idea is supported by the results of Gierach and colleagues, (30) who found an increased risk of death among obese women with non-dense breasts in a large cohort of U.S. women.…”
Section: Discussionmentioning
confidence: 86%
“…BD is essentially the ratio of fibroglandular tissue to fat. Three metrics that reflect the tissue composition of the breast commonly are used to characterize mammographic BD: 1) nondense area, which is breast fat tissue; 2) dense area, which is fibroglandular and stromal tissue; and 3) percentage density, which is the amount of dense tissue relative to the total breast area . Several factors are known to be associated with dense BD; among these are young age and premenopausal status, as well as the use of postmenopausal estrogen replacement .…”
Section: Introductionmentioning
confidence: 99%
“…Three metrics that reflect the tissue composition of the breast commonly are used to characterize mammographic BD: 1) nondense area, which is breast fat tissue; 2) dense area, which is fibroglandular and stromal tissue; and 3) percentage density, which is the amount of dense tissue relative to the total breast area. 3 Several factors are known to be associated with dense BD; among these are young age and premenopausal status, as well as the use of postmenopausal estrogen replacement. [4][5][6][7][8][9] In addition, it is hypothesized that there may be a genetic predisposition toward increased BD; however, to the best of our knowledge, the specific genetic factors remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Later menopause is associated with a higher risk of breast cancer, but also with lower risk of mortality 9 , 10 . One study reported an association of higher MD with lower mortality in women without breast cancer 11 . To explore the possibility that MD may reflect a reduced susceptibility to age-related disease, we examined whether MD was associated with blood telomere length (TL), a potential marker of susceptibility to chronic disease 12 .…”
Section: Introductionmentioning
confidence: 99%